AVIN: A Case Study on a Supporting Tool for the Self-Assessment Process in Higher Education Institutions - Araújo, Tiago Brasileiro; Vilar, Iriedson Souto Maior de Moraes; Cavalcanti, Gilvonaldo Alves da Silva; Felix, Ana Maria Alves; Santos, Emerson Andrey Fausto dos; Costa, Daniel dos Santos; Rodrigues, Rayane da Silva (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2025)
Brazilian Higher Education Institutions (HEIs) periodically undergo self-assessment processes to identify weaknesses and opportunities for improvement. These evaluations help analyze issues such as dropout rates, inadequate infrastructure, and student disengagement, supporting the development of strategic actions. This paper presents AVIN, a tool designed to facilitate this process by leveraging Business Intelligence (BI) concepts. AVIN enables HEIs to collect, process, and visualize data efficiently, providing reliable insights for decision-making. The tool aligns with the Ministry of Education self-assessment framework, integrating institutional participant groups to ensure accurate data retrieval and visualization.